Approximating a far-field blast environment in an advanced blast simulator for explosion resistance testing. Issue 4 (December 2020) - Gan, Edward Chern Jinn; Remennikov, Alex; Ritzel, David; Uy, Brian
While the current state of blast-resistant design methods is based largely on empirical observations of actual explosive testing or numerical simulations, experimental testing remains the ultimate method for validating blast protection technologies. Field trials for performing systematic experimental studies are exceedingly expensive and inefficient. Conventional blast simulators (shock tubes) enable blast testing to be performed in a safe and controlled laboratory environment but are significantly deficient. The Australian National Facility of Physical Blast Simulation based on the 'Advanced Blast Simulator' concept was established to address the shortcomings of conventional blast simulators (shock tubes). The blast simulator at the National Facility of Physical Blast Simulation is a state-of-the-art design having a test section of 1.5 × 2.0 m with dual-mode driver able of operating with either compressed gas or gaseous detonation modes. The simulator is capable of a range of blast-test configurations such as full-reflection wall targets and diffraction model targets. This article aims to demonstrate the ability of the Advanced Blast Simulator in accurately generating a far-field blast environment suitable for high-precision and repeatable explosion testing of various building components. Blast pressure-time histories generated with the Advanced Blast Simulator are validated against equivalent TNT free-field curves reproduced with Conventional Weapons Effects Program. Numerical models based on Computational Fluid Dynamics were developed in ANSYS FLUENT to accurately characterise and visualise the internal flow environment of the National Facility of Physical Blast Simulation Advanced Blast Simulator. The Computational Fluid Dynamics model was also used to explain experimental observations and to determine density and dynamic pressure information for comparisons with free-field explosion conditions.